Contract Reopeners - Danziger, Leif (Journal of Labor Economics, 1995)
This article incorporates contract reopeners into the analysis of contract duration and compares contracts with a reopener to contracts that cannot be reopened. The model contains relative and nominal shocks. It is shown that the stated duration of a reopenable contract is shortened by uncertainty associated with small shocks but lengthened by uncertainty associated with large shocks. However, the discounted expected duration decreases with the uncertainty associated with both small and large shocks. There exists a critical size of a large shock for which a reopenable contract and a contract with an immutable duration are equally attractive.